Microbial Inoculants for Improving Crop Quality and Human Health in Africa - Alori, Elizabeth Temitope; Babalola, Olubukola Oluranti (Frontiers in Microbiology, 2018)
Current agricultural practices depend heavily on chemical inputs (such as fertilizers, pesticides, herbicides, etc.) which, all things being equal cause a deleterious effect on the nutritional value of farm product and health of farm workers and consumers. Excessive and indiscriminate use of these chemicals have resulted in food contamination, weed and disease resistance and negative environmental outcomes which together have a significant impact on human health. Application of these chemical inputs promotes the accumulation of toxic compounds in soils. Chemical compounds are absorbed by most crops from soil. Several synthetic fertilizers contain acid radicals, such as hydrochloride and sulfuric radicals, and hence increase the soil acidity and adversely affect soil and plant health. Highly recalcitrant compounds can also be absorbed by some plants. Continuous consumption of such crops can lead to systematic disorders in humans. Quite a number of pesticides and herbicides have carcinogenicity potential. The increasing awareness of health challenges as a result of consumption of poor quality crops has led to a quest for new and improved technologies of improving both the quantity and quality of crop without jeopardizing human health. A reliable alternative to the use of chemical inputs is microbial inoculants that can act as biofertilizers, bioherbicide, biopesticides, and biocontrol agents. Microorganisms are able to carry out the plant growth promotion, pest and disease and weed control. Microbial inoculants are beneficiary microorganisms applied to either the soil or the plant in order to improve productivity and crop health. Microbial inoculants are natural-based products being widely used to control pests and improve the quality of the soil and crop, and hence human health. Microbial inoculants involve a blend of microorganisms that work with the soil and the soil life to improve soil fertility and health and by extension improve human health. Microbial inoculants have the ability to minimize the negative impact of chemical input and consequently increase the quantity and quality of farm produce. Microbial inoculants are environmental-friendly and deliver plant nutrients to plants in a more sustainable manner. Microbial inoculants can help reduce chemical fertilizer application. Microbial inoculants could include bacteria, fungi and algae. This research summarizes the impact of agricultural chemical inputs on human health. The contribution of microbial inoculants in sustainable maintenance of human health will be expatiated. Advances in microbial inoculants and technology and strategies to explore this natural, user friendly biological resource for sustainable maintenance of plant health will be discussed.